Penerapan DFMEA pada Perancangan Produk Casing Lampu Berbahan Dasar Bambu - Erik Odi Wijaya; Sahrupi Sahrupi; Mohamad Jihan Sofa (Operations Excellence: Journal of Applied Industrial Engineering, 2022)
This research aims to discover the higest impact of product failures and determine the proper of solution. Design FMEA is a method to anticipate failure during the design stage by identifying all of the possible failures in a design or manufacturing process. This studi conducted in a micro, small and medium-sized enterprises (SMEs). KIM is a small company that produce handycraft product made from bamboo plants, one of the featured product is lamp casing. Any of customers complain encourage the company to make new product design and look for the cause of the problem and risk. The results of this  research  are obtained 5 components of lamp casing with the highest level of risk. An Improvement was carried out entirely by using a repair priority scale according to the sequence of failure modes with the highest risk of damage.